Find the remainder when p(x) =4(x^3) -12(x^2) +14x-3 is divided by (2x-1).
Answers
Answered by
1
( 2x - 1 ) =0
x = 1 / 2
by remainder theorem..
now,
p ( 1/2 ) = 4 (1/2)^3 - 12 (1/2)^2 + 14(1/2) - 3
= 4 * 1/ 8 - 12 * 1/4 + 14 * 1/2 - 3
= 1 / 2 - 3 + 7 - 3
= 1/2 + 1
= 0.5 + 1 = 1.5 ans.
x = 1 / 2
by remainder theorem..
now,
p ( 1/2 ) = 4 (1/2)^3 - 12 (1/2)^2 + 14(1/2) - 3
= 4 * 1/ 8 - 12 * 1/4 + 14 * 1/2 - 3
= 1 / 2 - 3 + 7 - 3
= 1/2 + 1
= 0.5 + 1 = 1.5 ans.
Answered by
1
The answer is given below
Attachments:
![](https://hi-static.z-dn.net/files/d95/4dd98c63a0b35532bd8d69f574a51113.jpg)
Similar questions